Strategies for Curbing Gender-Stereotypes in Classroom Instructional Activities: Implication for Principals in Public Senior Secondary Schools in Akwa Ibom State - Love, Ebuk; O. L., Osaikuwuominan (Journal of Home Economics Research, 2024)
This paper focused on strategies for curbing gender stereotypes in classroom instructional activities: implication for principal in secondary schools in Akwa Ibom State. Survey research design was used for the study. The population of the study was 237 principals and 2948 teachers. The sample of the study was 400 respondents, using Yaro Yammane formula. Questionnaire was the instrument used to get information from the respondents. The findings of the study revealed that gender stereotypes were prevalent in public senior secondary schools and that principal supervisory strategies were used to curb gender stereotypes in classroom instructional activities in public senior secondary schools in Akwa Ibom State. It was therefore recommended by the researchers that: every teacher should avoid using derogatory gender stereotypes remarks on students during classroom instructional activities, school management should adopt effective supervisory styles that will encourage and promote gender equality in school that the school principals should not take supervision as fault finding but that it should be regard as guidance for teachers improvement. Principal supervisory style should be such that is gender friendly, so as to encourage and guide teachers during teaching.